Aktivitas Perkebunan di Kawasan Hutan Produksi Tetap Tanpa Izin Berusaha: Analisis Putusan Nomor 604/Pid.B/LH/2023/PN Rhl - Handoko, Juli; Sriono, Sriono; Siahaan, Nimrot (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aims to analyze Decision Number 604/Pid.B/LH/2023/PN Rhl regarding environmental crimes due to negligence in plantation activities within permanent production forest areas without a business permit. This normative legal research employs a statute approach and a case study. Data analysis uses a qualitative content analysis to describe the issues and answer the research objectives. The research results indicate that the prosecution of Defendant Turiono with alternative indictments in Decision Number 604/Pid.B/LH/2023/PN Rhl highlights the legal complexities of illegal plantations in permanent production forests. The first and second indictments were deemed inappropriate because they did not correspond to the facts and context of the case, particularly regarding the Defendant’s status as a wage labourer and the absence of mens rea. The Panel of Judges’ decision to apply Article 99 section (1) of Law Number 32 of 2009, with the element of negligence (culpa) and the principle of strict liability, was considered more appropriate, strengthening the protection of public interests and the prevention of environmental damage. This decision sets an important precedent by emphasizing the importance of considering the context and role of the perpetrator in environmental law enforcement, as well as its implications for preventing environmental crimes through permit verification and more systematic risk assessment.